An early assessment of CFPR II support packages - Das, Narayan Chandra; Raza, Wameq Azfar; Misha, Farzana Akter (BRAC Research and Evaluation Division, 2022)
Based on the programmatic lessons and research knowledge accumulated from CFPR phase I, CFPR phase II was designed to expand its outreach while incorporating greater diversity in support packages. The support packages of CFPR phase II are primarily divided into two groups: Specially Targeted Ultra Poor (STUP) and Other Targeted Ultra Poor (OTUP). STUP and OTUP packages were further disaggregated into STUP 1 and 2 and OTUP 1 and 2. This paper presents an early assessment of the performance of the CFPR phase II support packages. For STUP 1 assessment, a Randomized Control Trial (RCT) method was used. For STUP 2 and OTUP 1 and 2 packages, the assessment was conducted by comparing old and new cohorts. STUP 1 package was found to have significant positive impacts on the livelihoods of the participating households. Evidence shows that as a result of program participation, the STUP 1 households experienced an increase in farm self-employment for both males and females, diversification of income sources, increase in per capita income and food expenditure, and increase in saving behaviour. STUP 2 and OTUP 1 and 2 packages, assessed using the same method, were also found to have positive impacts on livelihoods of the participating households although the dimensions and magnitude of impacts varied within the packages. Effectiveness of OTUP 2 package was found to be the lowest amongst these three packages. This is, however, expected as OTUP 2 package is significantly less intensive than the STUP 2 and OTUP 1. On the other hand, the efficacy of the STUP 2 and OTUP 1 packages was found to be quite similar despite the STUP 2 package being more intensive of the two. The STUP 2 households, as was found in this study, experienced loss of livestock and poultry due to hurricane Sidr, which might have slowed down the effectiveness of this package.